A different background of arrhythmia in siblings with a positive family history of sudden death at young age. Issue 4 (14th October 2019) - Stępień‐Wojno, Małgorzata; Franaszczyk, Maria; Bodalski, Robert; Śpiewak, Mateusz; Baranowski, Rafał S.; Grzybowski, Jacek; Płoski, Rafał; Bilińska, Zofia T.
Abstract: We present two symptomatic sisters who had a positive family history of sudden death. None of them had structural heart disease. In the 25‐year‐old proband, complex ventricular arrhythmia, cardiac conduction system disease, and skeletal muscle weakness were found. Genetic examination showed a pathogenic intronic variant in the desmin gene in the proband only. In the elder sister with palpitations, complex ventricular arrhythmia (>46 000 ectopic beats) was removed by radiofrequency ablation. This family case shows that complex ventricular arrhythmia may have different background within one family, genetic examinations should be performed in a person with broadest spectrum of symptoms.